Die Biologie von Elasmucha grisea L. (Heteroptera: Acanthosomidae). - Jordan, Carl Hermann Christian (Contributions to Entomology = Beiträge zur Entomologie, 1958)
The author describes the life habits of the bug Elasmucha grisea L. providing for succeeding generations. There are given details on copula, oviposition, and behaviour of larvae. It is shown, how the larvae are enabled to provide themselves with symbionts. The hitherto unknown phonation of the male before copulating is discussed and traced back to motions of the wall of the abdomen. Finally the author deals with the systematic position of the subfamily Acanthosominae stating the reasons of the necessitiy to give it family rank.